INTERNATIONALIZATION OF CONFLICT AS A CHALLENGE TO PEACE AND DEVELOPMENT IN AFRICA - ANTHONY IMEH UMOH; BARINAADAA NWINKOL (International Studies Journal)
It is an indubitable fact that African countries has been highly susceptible to inter and intra conflicts after independence. This has made Africa to be christened the hub of conflicts and wars. Most pathetic is the fact that these conflicts and wars have defied any meaningful solution, and their negative impact has impeded peace and development in the continent. It has eroded to a larger extent the core value of human existence in the continent. The depended nature of African economy is largely blame for this, knowing fully well that whatever affects he developed nations have a rippling effect on Africa. This paper examines the challenges the internationalization of conflict has posed to peace and development in Africa. The paper argues that most of the violent conflict in the continent has external influence and sponsors. It blames the Cold War rivalry between the capitalist United States and the communist USSR as it were, where attempt by the African allies to delink from either of the ideologies to favour the other, always led to intervention by these powerful nations. The paper submits that while the external factors share in the blame for Africa lack of peace, development and progress, African leaders are largely to blame for the myriads of problems that have bedeviled the continent due to their tantrum for bad leadership.